Soil Aggregation Shaped the Distribution and Interaction of Bacterial-Fungal Community Based on a 38-Year Fertilization Experiment in China - Chen, Jie; Song, Dali; Liu, Donghai; Sun, Jingwen; Wang, Xiubin; Zhou, Wei; Liang, Guoqing (Frontiers in Microbiology, 2022)
Soil aggregates provide different ecological niches for microorganisms, and in turn, the microbial interactions affect soil aggregation process. The response of the microbial community in bulk soil to different fertilization regimes has been well studied; however, the co-occurrence patterns of bacteria and fungi in different aggregates under various fertilization regimes remain unclear. Based on the long-term field experiment, we found that fertilization regimes contributed more to fungal than to bacterial community composition. Long-term fertilization decreased microbial interactions in large macroaggregates (LM), macroaggregates (MA) and silt and clay (SC) fractions, but increased in microaggregates (MI). The application of manure with inorganic fertilizers (NPKM) significantly increased the intensive cooperation between bacteria and fungi in LM and MA. Microbial communities in LM and MA were well separated and showed strong competition against microbes in MI and SC; hence, we concluded that the microbial habitat could be divided into two groups, large fractions (LM and MA) and small fractions (MI and SC). The bacterial genera Anaerolinea, Nocardioides, Ohtaekwangia, Geoalkalibacter, Lysobacter, Pedomicrobium and Flavisolibacter were keystone taxa in inorganic fertilization, and Roseiflexus, Nitrospira and Blastocatella were keystone taxa in NPKM, which were all sensitive to soil aggregation. In this study, we demonstrated that the NPKM decreased the microbial interactions within and between kingdoms in LM, MA, and SC, but enhanced nutrient availability and microbial interactions in MI, leading to the formation of biofilms and the strengthening of stress tolerance, which finally stimulated the formation and stabilization of soil aggregates. Thus, this study revealed how soil microbial competition or cooperation responded to different fertilization regimes at aggregate scales, and provided evidence for the stimulation of soil stability.